2023
DOI: 10.3389/fneur.2023.1256745
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the autoantibody repertoire reveals autoantibodies associated with mild cognitive impairment and dementia

Hanan Ehtewish,
Areej Mesleh,
Georgios Ponirakis
et al.

Abstract: BackgroundDementia is a debilitating neurological disease affecting millions of people worldwide. The exact mechanisms underlying the initiation and progression of the disease remain to be fully defined. There is an increasing body of evidence for the role of immune dysregulation in the pathogenesis of dementia, where blood-borne autoimmune antibodies have been studied as potential markers associated with pathological mechanisms of dementia.MethodsThis study included plasma from 50 cognitively normal individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…The authors also showed that the autoantibody panel was highly specific for MCI, such that it distinguished between participants with AD-associated MCI and those with other neurodegenerative diseases (e.g., Parkinson's disease, multiple sclerosis) and non-neurodegenerative conditions (e.g., early-stage breast cancer). In a recent study, Ehtewish et al [67] explored the plasma autoimmune profile of 127 older adults of whom 50 were cognitively healthy, 55 had MCI, and 22 had a diagnosis of dementia. Differential expression analysis revealed 33 dysregulated plasma autoantibodies in participants with dementia compared with cognitively healthy controls, while 38 dysregulated autoantibodies differentiated individuals with dementia from those with MCI.…”
Section: Proteomic Biomarkersmentioning
confidence: 99%
“…The authors also showed that the autoantibody panel was highly specific for MCI, such that it distinguished between participants with AD-associated MCI and those with other neurodegenerative diseases (e.g., Parkinson's disease, multiple sclerosis) and non-neurodegenerative conditions (e.g., early-stage breast cancer). In a recent study, Ehtewish et al [67] explored the plasma autoimmune profile of 127 older adults of whom 50 were cognitively healthy, 55 had MCI, and 22 had a diagnosis of dementia. Differential expression analysis revealed 33 dysregulated plasma autoantibodies in participants with dementia compared with cognitively healthy controls, while 38 dysregulated autoantibodies differentiated individuals with dementia from those with MCI.…”
Section: Proteomic Biomarkersmentioning
confidence: 99%